Final Disposal of Urban Solid Waste and the Generation of Greenhouse Gases in the State of Pará - Soares Almeida, Fernando Felipe; Rodrigues Pereira, José Almir (National Journal of City Management, 2023)
This paper presents the a study about the emission of greenhouse gases - GHG resulting from the final disposal of urban solid waste - USW in the State of Pará. The research was qualitative and quantitative, applied in nature and with exploratory and descriptive objectives, having as object of study the solid waste sector in the State of Pará. The activities carried out were divided into 3 stages, with the verification of the amount of GHG emissions in the State of Pará (Stage 1), the contribution of the sectors responsible for the state’s emissions (Stage 2) and the analysis of GHG emissions in the USW sector (Stage 3). The survey results show that Pará is the state that emits the most GHG in Brazil (447,927,368 tons of CO2e). Although the USW sector accounts for only 1% of GHG, it was found that 138 of the 144 municipalities in Pará still send USW to dumps and controlled landfills. With the research, it was verified the need to adapt the environmentally-appropriate final destination of USW, as an alternative to reduce GHG emissions in the State of Pará.